Metal(loid) pollution, not urbanisation nor parasites predicts low body condition in a wetland bioindicator snake - Lettoof, Damian; Cornelius, Jari; Jolly, C.J.; Aubret, Fabien; Gagnon, Monique; Hyndman, T.H.; Barton, D.P.; Bateman, Bill (2022)
Urban ecosystems and remnant habitat 'islands' therein, provide important strongholds for many wildlife species including those of conservation significance. However, the persistence of these habitats can be undermined if their structure and function are too severely disrupted. Urban wetlands, specifically, are usually degraded by a monoculture of invasive vegetation, disrupted hydrology, and chronic-contamination from a suite of anthropogenic pollutants. Top predators—as bioindicators—can be used to assess and monitor the health of these ecosystems. We measured eight health parameters (e.g., parasites, wounds and scars, tail loss and body condition) in a wetland top predator, the western tiger snake, Notechis scutatus occidentalis. For three years, snakes were sampled across four wetlands along an urban gradient. For each site, we used GIS software to measure the area of different landscapes and calculate an urbanisation–landscape score. Previously published research on snake contamination informed our calculations of a metal-pollution index for each site. We used generalised linear mixed models to assess the relationship between all health parameters and site variables. We found the metal-pollution index to have the most significant association with poor body condition. Although parasitism, tail loss and wounds differed among sites, none of these parameters influenced body condition. Additionally, the suite of health parameters suggested differing health status among sites; however, our measure of contemporary landscape urbanisation was never a significant predictor variable. Our results suggest that the health of wetland predators surrounding a rapidly growing city may be offset by higher levels of environmental pollution.